Montelukast attenuates interleukin IL-1β-induced oxidative stress and apoptosis in chondrocytes by inhibiting CYSLTR1 (Cysteinyl Leukotriene Receptor 1) and activating KLF2 (Kruppel Like Factor 2). Issue 1 (1st January 2021) - Li, Zongwei; Wang, Jianming; Ma, Yumin
ABSTRACT: Montelukast is a cysteinyl leukotriene receptor 1 (CysLTR1) antagonist widely used to suppress the inflammatory response in asthma and allergic rhinitis. This study aimed to investigate the potential impacts of montelukast on osteoarthritis (OA) progression. To determine the role of montelukast in OA, the expression of CysLTR1 was first examined by quantitative reverse transcription PCR (RT-qPCR) and western blot in IL-1β-induced ATDC5 cells treated with or without montelukast. Subsequently, the impacts of montelukast on cell viability and oxidative stress were measured by Cell-Counting-Kit-8 (CCK-8), commercial kits and western blot. Oxidative stress-related protein expressions were determined by western blot analysis in Il-1β-induced ATDC5 cells. Cell apoptosis and cartilage degradation were examined by TdT-mediated dUTP Nick-End Labeling (TUNEL) assay, western blot and RT-qPCR. KLF2 expression was measured in IL-1β-induced ATDC5 cells treated with montelukast. After interference with small interfering RNA (siRNA)-KLF2 in ATDC5 cells, the loss-of-function assays were also performed in same ways. CysLTR1 expression was elevated in IL-1β-induced ATDC5 cells but inhibited significantly by montelukast. Montelukast attenuated the oxidative stress and apoptosis, improved cell viability. Moreover, montelukast enhanced KLF2 expression. After transfected with siRNA-KLF2, montelukast attenuated cell injury, oxidative stress, apoptosis and cartilage degradation in IL-1β-induced ATDC5 cells by activating KLF2.In summary, this work elaborates the evidence that montelukast could attenuate oxidative stress and apoptosis in IL-1β-induced chondrocytes by inhibiting CysLTR1 and activating KLF2, which can guide the therapeutic strategies of montelukast for OA development in the future.